Government Incentive Contracts for Microgrid Users - Guanyi Yu; Qiang Lin; Xiaoqian Qi (Energies, 2021)
Tariff subsidies are beneficial to the further development of the microgrid market. In response to the reduction of the power generation costs of microgrids, the energy storage subsidy for microgrids has become a key factor affecting their further development. Therefore, it is essential to explore and establish a government subsidy mechanism for the energy storage price of microgrids. In this paper, we consider the incentive compatibility constraints and participation constraints of both the government and the microgrid energy storage subsidy. The cases of hidden information and no hidden information are investigated. A microgrid energy storage subsidy model of the incentive compatibility constraint was established to analyze the efficiency of the government subsidy and the microgrid energy storage in the “self-generation + energy storage” mode. The results show that there is an adverse selection problem between the government and energy storage subsidies for microgrid users. In the case of no hidden information, the government can sign different contracts with microgrid users according to their different energy storage efficiency levels. In the case of hidden information, it is better for the government to design a menu of different incentive contracts for microgrid users with different energy storage efficiencies. This approach can ensure that microgrid users with low energy storage efficiency continue to participate in the microgrid construction. Microgrid users with high energy storage efficiency can, thus, better control their costs related to the self-generation, self-use, and surplus electricity transmitted to the grid as well as better select high-regulation carbon dioxide emission reductions and their capacity generation.